The strategies of China's firms : resolving dilemmas - Yang, Hailan; Morgan, Stephen L.; Wang, Ying (Elsevier Asian studies series., 2015)
This book aims to analyze how China's firms in the consumer electronics (CE) sector have developed their business strategy and corporate governance during the reform process. This book examines the CE sector in particular because it is one of the country's most important and dynamic manufacturing sectors and one of the earliest market-oriented sectors.